EVALUASI PELAKSANAAN PROGRAM DESA MANDIRI PANGAN (DEMAPAN) DI KELURAHAN TOBIMEITA KECAMATAN ABELI KOTA KENDARI - Sukmawati Abdullah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This research was conducted from July to August of 2013 with the aim to analyze and to evaluate the empowerment of the poor in managing and utilizing the resources possessed optimally through the implementation of the Desa Mandiri Pangan’s program in Tobimeita Village Abeli ​​District of Kendari. The technique of determining the sample was done by proportional random sampling in four affinity groups and one group of non-affinity with a total sample of 29 people. The research design was a survey approach by using secondary and primary data, both quantitative and qualitative. The Data analysis method used in this research was descriptive qualitative analysis. The results of the research indicate that the preparation stage has conducted the selection of location, the determination of the companion, the establishment and determination of the village food team, the preparation of the basic data of the village, the establishment and growth of Kembaga Keuangan Desa (LKD), organizing and mentoring activities, the preparation of the Lembaga Keuangan Desa (RPWD), training on program implementation preparation, and channeling the sosial assistance fund. The level of growth has conducted the training activities, increased accessibility of community, strengthened institutional, developed the food security system, strengthened the Dasa Wisma, and supported the facilities and infrastructure. At the stage of development has been doing the skills upgrading and accessing to capital, the growth of food reserves, the utilization of food resources, and the development of facilities and infrastructure. The conclusion of this research result shows that the program implementation of Desa Mandiri Pangan in the village of Tobimeita starts from the preparation stage in the first year, the growth stage in the second year until the third year of development phase has been going well